Pro-WEAI complementary indicators for nutrition- sensitive agriculture and market inclusion projects - Malapit, Hazel; Heckert, Jessica (2023)
Hazel Malapit and Jessica Heckert POLICY SEMINAR Introducing pro-WEAI complementary indicators for nutrition- sensitive agriculture and market inclusion projects MAR 2, 2023 - 9:00 TO 10:30AM EST